Myocardial Impact of NHE1 Regulation by Sildenafil - Escudero, Daiana S.; Pérez, Néstor G.; Díaz, Romina G. (Frontiers in Cardiovascular Medicine, 2021)
The cardiac Na+/H+ exchanger (NHE1) is a membrane glycoprotein fundamental for proper cell functioning due its multiple housekeeping tasks, including regulation of intracellular pH, Na+ concentration, and cell volume. In the heart, hyperactivation of NHE1 has been linked to the development of different pathologies. Several studies in animal models that reproduce the deleterious effects of ischemia/reperfusion injury or cardiac hypertrophy have conclusively demonstrated that NHE1 inhibition provides cardioprotection. Unfortunately, NHE1 inhibitors failed to reproduce these effects in the clinical arena. The reasons for those discrepancies are not apparent yet. However, a reasonable clue to consider would be that drugs that completely abolish the exchanger activity, including that its essential housekeeping function may not be the best therapeutic approach. Therefore, interventions tending to specifically reduce its hyperactive state without affecting its basal activity emerge as a novel potential gold standard. In this regard, a promising goal seems to be the modulation of the phosphorylation state of the cytosolic tail of the exchanger. Recent own experiments demonstrated that Sildenafil, a phosphodiesterase 5A inhibitor drug that has been widely used for the treatment of erectile dysfunction is able to decrease NHE1 phosphorylation, and hence reduce its hyperactivity. In connection, growing evidence demonstrates cardioprotective properties of Sildenafil against different cardiac pathologies, with the distinctive characteristic of directly affecting cardiac tissue without altering blood pressure. This mini-review was aimed to focus on the regulation of NHE1 activity by Sildenafil. For this purpose, experimental data reporting Sildenafil effects in different animal models of heart disease will be discussed.